Reporting skyline on uncertain dimension with query interval - Mohd Saad, Nurul Husna; Ibrahim, Hamidah; Sidi, Fatimah; Yaakob, Razali; Alwan Aljuboori, Ali Amer (Universiti Teknikal Malaysia Melaka, 2016)
Naturally, users sometimes specify their preference in an imprecise way (i.e. query with an interval/range). To report results that satisfy the imprecise query as well as interesting would be easy on dataset with atomic values. The challenge is when the dataset being queried consists of both atomic values as well as continuous range of values. For a set of objects with uncertain dimension and given a query interval [qi,qi'] on that uncertain dimension, a skyline query on that interval returns the objects which are not dominated by any other objects in the query interval. A method is proposed to help determine objects that intersect with the query interval and answer skyline query that satisfy the query interval. The correctness of the method is proven through comparisons between two methods that strictly reject and loosely accept objects from/into the query interval.